Measuring Transnationality of Immigrants in Germany: Prevalence and Relationship with Social Inequalities - Margit Fauser; Elisabeth Liebau; Sven Voigtländer; Hidayet Tuncer; Thomas Faist; Oliver Razum (Ethnic and Racial Studies, 2015)
The scope of immigrants' transnational ties and the relationship to their social position is subject to a controversial debate that suggests a dualistic picture. On the one hand, globalization theorists argue that an elite of highly educated and economically most successful professionals intensively engages in and benefits from transnationality. On the other hand, most scholars in migration and assimilation studies hold that it is the most underprivileged immigrants who maintain strong ties across state borders, which in turn furthers their marginalization. Yet, to date, very little systematic research has been conducted into the nexus between social inequalities and transnationality. This paper aims to fill this gap. Using data from the German Socio-Economic Panel (SOEP), we show that the economic, cultural and social forms of capital are related to transnationality in different ways, rather than reflecting one uniform pattern.
Additional information: This is an Accepted Manuscript of an article published by Taylor & Francis in Ethnic and Racial Studies vol. 38 (2015), iss. 9, p. 1497-1519, available online at http://www.tandfonline.com/doi/full/10.1080/01419870.2015.1005639
Keywords: 330; migrants; transnationality; inequality; Germany; capital; heterogeneity